Die Integration prosodischen und syntaktischen Wissens bei der Ermittlung der Textkohärenz im schriftlichen Textverstehen - Cosentino, Gianluca (Linguistik Online, 2022)
Reading is a highly complex cognitive process. From a neurobiological point of view, it involves at least six linguistic sub-competences including orthographic, semantic, syntactic, phonetic and prosodic competence. Each of these skills is required of the reader to extract different types of information from the text, ranging from the perceptual and the syntactic to the lexical and pragmasemantic one.Based on the main results of cognitive-oriented research on text and reading, this paper illustrates how prosodic competence, combined with formal coherence patterns, can be considered and employed as a reading strategy, enabling the reader to progressively grasp the meanings of a text. In the first part particular attention will be paid to the description of the syntax-prosody interface as well as of its function as a means of encoding of information structure in German. With regard to the teaching of German as a foreign language, the second part of the paper will present a method to train intonational reading. This approach aims to raise foreign language readers’ awareness of prosodic features of written texts and to introduce them to melodic patterns which can be encountered while reading. Such a practical training may prove to be advantageous, as the most typical and apparently “uncorrectable” errors committed by foreign language learners when speaking and reading German texts are almost always related to the domains of phonology and prosody.